IMPLEMENTASI METODE MURAJA’AH SEBAGAI KARAKTERISASI DISIPLIN SISWA MELALUI HAFALAN KITAB ALFIYYAH IBNU MALIK DI MA NU MIFTAHUL FALAH KUDUS: - Putri, Yunita Ardila; Efferi, Adri (Al’ulum Jurnal Pendidikan Islam, 2025)
This study aims to describe the implementation of the muroja’ah method in the memorization program of the Kitab Alfiyyah Ibnu Malik at MA NU Miftahul Falah Cendono Dawe Kudus and its contribution to shaping students' discipline character. This research employed a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The results show that the scheduled and continuous application of muroja’ah has a significant impact on strengthening student discipline. Students involved in the program demonstrate the ability to manage their time, maintain consistency in memorization, and take responsibility for achieving set targets. The program's success is supported by institutional commitment, active involvement of teachers, and parental support. Despite challenges such as boredom and time conflicts with other activities, teacher motivation and regular evaluations help sustain the program. Thus, the muroja’ah method not only serves as a memorization strategy but also acts as an effective character-building tool, particularly in fostering discipline among students within the Islamic education environment.